Ruptured Pericallosal Artery Aneurysm: A Case Report - I Wayan Niryana; Made Bhuwana Putra; Christopher Lauren; Yosep Mote; I Gusti Ketut Agung Surya Kencana (Caspian Journal of Neurological Sciences)
Background: Pericallosal artery aneurysm (PCA) is a rare intracranial aneurysm, accounting for 2–9% of all cases, with only 4% of these rupturing. Despite their small size, PCA aneurysms have a higher rupture risk compared to other anterior circulation aneurysms. Surgical management, particularly clipping via interhemispheric approaches, poses significant challenges and risks. This report discusses a case of ruptured PCA aneurysm managed successfully through microsurgical intervention. Case Presentation: A 47-year-old woman presented with a week-long history of intense headache. Initial evaluation revealed a Glasgow Coma Scale score of 15 and positive signs of meningeal irritation. CT imaging showed subarachnoid hemorrhage, and CT angiography confirmed a saccular aneurysm in the left pericallosal artery. Classified as Hunt and Hess grade 2, the patient underwent aneurysm clipping via an anterior interhemispheric approach. The operation included bifrontal craniotomy, meticulous arachnoid dissection and clip application, confirmed with intraoperative fluorescence. Postoperatively, the patient demonstrated an uneventful recovery with no neurological deficits or rebleeding during a 3-year follow-up period. Conclusion: This case highlights the challenges of managing PCA aneurysms, emphasizing microsurgical clipping as a safe and effective treatment, particularly in resource-limited settings. Early surgical intervention, meticulous operative planning, and follow-up are critical for optimizing outcomes and minimizing complications.